Impacts of Firm Internationalization, Corporate Governance, and Financial Performance on Dividend Policy — A Case Study of Taiwan Listed Firms - Lin, Tse-Mao; Yu, Jing-Long; Yang, Meng-Ying; Huang, Chin-Sheng (International Journal of Finance Research, 2022)
The capital market considers the corporate governance system when evaluating and investing in firms to cope with changes and challenges from firm internationalization. In response to the need for global economic development, Taiwan firms have enhanced their competitiveness to meet international standards and link with the world economy. A good corporate governance mechanism can bring good operating performance to a firm. The cash dividends declared each year reflects the operating status of the firm and explains its profitability and value each year, providing relevant and significant information for institutional and ordinary investors to make investment decisions. This study took Taiwan listed firms as the research object. Based on the annual data from 2005 to 2019 in the enterprise business database of the Taiwan Economic Journal, constructed a panel data regression model combining time-series and cross-sectional data. The aim was to empirically investigate and analyze the correlation of firm internationalization, corporate governance, and financial performance indicators with corporate cash dividend payouts. The findings showed that after the variables of firm internationalization, financial performance, and corporate governance were combined, the export ratio (a variable representing firm internationalization) positively impacted corporate dividend payouts. In other words, the higher degree of internationalization, the more cash dividends paid by the firm. In corporate governance, a firm with a higher shareholding ratio of financial institutions showed significantly more cash dividends. Regarding financial performance indicators, a firm with higher recurring earnings per share showed significantly fewer cash dividends